Dual-source RF transmission in cardiac SSFP imaging at 3 T: Systematic spatial evaluation of image quality improvement compared to conventional RF transmission - Rasper, Michael; Gramer, Bettina M.; Settles, Marcus; Laugwitz, Karl-Ludwig; Ibrahim, Tareq; Rummeny, Ernst J.; Huber, Armin (Clinical Imaging, 2015)
The purpose of this investigation was to systematically evaluate the spatial distribution of image quality improvement with dual-source radiofrequency (RF) transmission in cardiac steady-state free precession sequences at 3.0 T. Imaging with and without dual-source RF transmission was performed in 30 patients. Contrast-to-noise ratio for the left ventricular myocardium was significantly higher using dual-source RF transmission, but improvement was not uniformly distributed. The posterior myocardium showed significantly less contrast-to-noise ratio gain than all other cardiac regions. Signal-to-noise ratio increase was higher in the right than in the left ventricle. Subjective image quality was significantly enhanced by parallel RF transmission.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cardiac MRI; Dual-source RF transmission; MultiTransmit; SSFP